Variability in the drivers of microplastic consumption by fish across four lake ecosystems - Conowall, Peter; Schreiner, Kathryn M.; Marchand, Joseph; Minor, Elizabeth C.; Schoenebeck, Casey W.; Maurer-Jones, Melissa A.; Hrabik, Thomas R. (Frontiers in Earth Science, 2024)
Abstract Microplastic (< 5mm) pollution has been documented globally throughout freshwater and marine ecosystems. Exposure to and ingestion of microplastics presents a threat to the health of aquatic and marine organisms and humans through the consumption of fish and crustaceans. Understanding the factors which influence microplastic ingestion by fish is a key step in predicting the potential health risks. Drivers of microplastic consumption have been studied in lab settings, but there has been limited ability to confirm in field studies. Here we examine the roles and contributions of feeding guild, pelagic microplastic concentrations, and fish length to microplastic consumption by three species of fish across four lake ecosystems in Minnesota, USA. Fish samples were collected in the summers of 2019 and 2020 and processed to determine variability in microplastic ingestion. Identifying particles between 0.18 mm and 5.00 mm, plastic ingestion ranged from 0.6 microplastics fish-1 in Elk Lake (low surface water microplastics) bluegill to 1.09 microplastics fish-1 in White Iron Lake (moderate surface water microplastics) cisco. Results indicate that microplastic consumption by filter feeding cisco is driven by surface water microplastic concentrations, while microplastic consumption by visual feeding bluegill and yellow perch is not. Additionally, the high variability of ingestion between lake ecosystems coupled with the complex behavior of some fish species presents difficulties in identifying primary drivers of microplastic consumption that would be broadly applicable across ecosystems and species.